Antibacterial activity of antileukoprotease. - Hiemstra, P S (1996)
Antileukoprotease (ALP), or secretory leukocyte proteinase inhibitor, is an endogenous inhibitor of serine proteinases that is present in various external secretions. ALP, one of the major inhibitors of serine proteinases present in the human lung, is a potent reversible inhibitor of elastase and, to a lesser extent, of cathepsin G. In equine neutrophils, an antimicrobial polypeptide that has some of the characteristics of ALP has been identified (M. A. Couto, S. S. L. Harwig, J. S. Cullor, J. P. Hughes, and R. I. Lehrer, Infect. Immun. 60:5042-5047, 1992). This report, together with the cationic nature of ALP, led us to investigate the antimicrobial activity of ALP. ALP was shown to display marked in vitro antibacterial activity against Escherichia coli and Staphylococcus aureus. On a molar basis, the activity of ALP was lower than that of two other cationic antimicrobial polypeptides, lysozyme and defensin. ALP comprises two homologous domains: its proteinase-inhibitory activities are known to be located in the second COOH-terminal domain, and the function of its first NH2-terminal domain is largely unknown. Incubation of intact ALP or its isolated first domain with E. coli or S. aureus resulted in killing of these bacteria, whereas its second domain displayed very little antibacterial activity. Together these data suggest a putative antimicrobial role for the first domain of ALP and indicate that its antimicrobial activity may equip ALP to contribute to host defense against infection.